DEVELOPING A SET MODULE WITH A GUIDED INQUIRY AND TAHFIDZUL QURAN TO IMPROVE STUDENTS’ CRITICAL THINKING - Akhmad Syahwanul Karim; Yus Mochamad Cholily; Mohammad Syaifuddin (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2021)
This research aimed to develop a set module with a guided inquiry and Tahfidzul Quran (Quran memorization) to improve students' critical thinking. This research was a Research and Development (R&D) based on the ADDIE Model with a one-group of pre-test and post-test design conducted for Year-7 students at an Islamic Boarding School in Malang, East Java. The subjects in this study were 12 students. Three aspects were present in this module development: process, quality, and effectiveness. The results of this study showed that (1) The development of the set module with a guided inquiry approach and the Tahfidzul Quran process refers to the ADDIE development model with the following steps: analysis, design, development, implementation, and evaluation; (2) The set module has a suitable quality of use as the learning module satisfying the aspects of content, presentation, language, graphics, and tahfidz; (3) The use of the set module with the guided inquiry approach and Tahfidzul Quran is effective in improving students' critical thinking. The students’ responses to the learning module were positive. In conclusion, a set module developed with the guided inquiry and Tahfidzul Quran to improve students' critical thinking has fulfilled the rules of process, quality, and effectiveness.